Reirradiation of head and neck cancer: Long‐term disease control and toxicity. Issue 6 (6th March 2017) - Bots, Wouter T. C.; van den Bosch, Sven; Zwijnenburg, Ellen M.; Dijkema, Tim; van den Broek, Guido B.; Weijs, Willem L. J.; Verhoef, Lia C. G.; Kaanders, Johannes H. A. M.
ABSTRACT: Background: The purpose of this study was to report long‐term disease control and late radiation toxicity for patients reirradiated for head and neck cancer. Methods: We conducted a retrospective analysis of 137 patients reirradiated with a prescribed dose ≥45 Gy between 1986 and 2013 for a recurrent or second primary malignancy. Endpoints were locoregional control, overall survival (OS), and grade ≥4 late complications according to European Organization for Research and Treatment of Cancer (EORTC)/Radiation Therapy Oncology Group (RTOG) criteria. Results: Five‐year locoregional control rates were 46% for patients reirradiated postoperatively versus 20% for patients who underwent reirradiation as the primary treatment ( p < .05). Sixteen cases of serious (grade ≥4) late toxicity were seen in 11 patients (actuarial 28% at 5 years). In patients reirradiated with intensity‐modulated radiotherapy (IMRT), a borderline improved locoregional control was observed (49% vs 36%; p = .07), whereas late complication rates did not differ. Conclusion: Reirradiation should be considered for patients with a recurrent or second primary head and neck cancer, especially postoperatively, if indicated. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1122–1130, 2017